PENGARUH HARGA, LOKASI, DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADATOKO PERHIASAN SARI INTAN ASEMBAGUS SITUBONDO - Arandita, Reza Mevia; Ediyanto, Ediyanto; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Marketing is a process of business activities to introduce a product to consumers and customers. The purpose of this study was to analyze and test the effect of price, location, and service quality in determining customer loyalty with purchasing decisions as an intervening variable. The population in the study were consumers of Sari Intan Asembagus Situbondo Jewelry Store. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in the study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3. 0, shows that Price has a significant positive effect on purchasing decisions; Location has a significant positive effect on purchasing decisions; Service quality has a negative and insignificant effect on purchasing decisions; Price has a negative and insignificant effect on customer loyalty; Location has a significant positive effect on customer loyalty; Service quality has a negative and insignificant effect on customer loyalty; Purchasing decisions have a negative and insignificant effect on customer loyalty; Price has a negative and insignificant effect on customer loyalty through purchasing decisions; Location has a negative and insignificant effect on customer loyalty through purchasing decisions; Service quality has a negative and insignificant effect on customer loyalty through purchasing decisions.